A Five-Day Intensive Treatment for Pediatric Obsessive-Compulsive Disorder: A Multiple Baseline Design Pilot Study. Issue 1 (2nd January 2023) - Canavera, Kristin E.; Ollendick, Thomas H.; Farrell, Lara J.; Whiteside, Stephen P. H.
ABSTRACT: The need for effective treatments for obsessive-compulsive disorder (OCD) in childhood is evident given that as many as 50% of the adults with OCD report symptom onset before age 15. Despite the growing evidence supporting the efficacy of Exposure and Response Prevention (ERP) for youth with OCD, children seeking services for their OCD symptoms often do not receive ERP because of difficulties with treatment accessibility. Brief time-intensive treatment programs may be a feasible treatment option for children and their families who do not have access to ERP treatment and/or live in an area where therapists trained in ERP are limited. To evaluate the initial efficacy, feasibility, and acceptability of a brief, five-day intensive ERP program for pediatric OCD, eight children with OCD were randomized to a one-week, two-week, or three-week baseline period in a single-case, non-concurrent multiple-baseline experimental design. In most cases, there were clinically significant improvements in OCD symptoms with the implementation of treatment; moreover, treatment gains were maintained at 3-month follow-up. Children and families perceived the program to be acceptable, feasible, and beneficial. This study extends the support for the efficacy and feasibility of a five-day intensive treatment program for pediatric OCD.